Proceedings of the 25th ACM SIGSPATIAL International Conference on Advances in Geographic Information Systems 2017
DOI: 10.1145/3139958.3139976
|View full text |Cite
|
Sign up to set email alerts
|

Feature-centric ranking algorithms for georeferenced video search

Abstract: While it is commonplace to retrieve photos showing a particular feature (e.g. through tools such as Google Pictures or Bing Images), spatial approaches for retrieving videos showing a particular feature (e.g. a building) have yet to be established. is article proposes ve ranking algorithms to query georeferenced videos for a speci c feature based on the videos' spatio-temporal metadata. 12 relevance criteria for feature-centric video ranking were compiled from a focus group discussion. From these, four criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Relevance ranking has been examined for georeferenced videos in [1,19]. Ay et al [1] proposed algorithms for ranking of videos based on their spatial and temporal properties, and Fritze et al [19] reported on 12 criteria suggested by users to determine the relevance of georeferenced videos. Despite these works, and work examining geographic relevance (e.g.…”
Section: Relevance In Girmentioning
confidence: 99%
“…Relevance ranking has been examined for georeferenced videos in [1,19]. Ay et al [1] proposed algorithms for ranking of videos based on their spatial and temporal properties, and Fritze et al [19] reported on 12 criteria suggested by users to determine the relevance of georeferenced videos. Despite these works, and work examining geographic relevance (e.g.…”
Section: Relevance In Girmentioning
confidence: 99%